Kajian Pelayanan Pelaksanaan On The Job Trainining (OJT) Taruna di Politeknik Penerbangan Indonesia Curug Tangerang - Endang Sugih Arti; Dini Wagini (Politeknik Penerbangan Indonesia Curug, 2020)
This study discusses the implementation services of OJT cadets at PPI Curug. The research method used is descriptive analysis, namely analyzing the problem of lecturers' anxiety about the implementation of OJT cadets and the data collection methods are interviews, literature study and questionnaires by distributing question sheets to OJT Instructors at 24 airports as OJT locations in Perum LPPNPI. Furthermore, the data is measured according to the Slovin formula with an error rate of 5%. This study aims to determine the conditions of service for the implementation of OJT for cadets at PPI and to find out the obstacles that occur in it and to find alternative solutions. The results obtained from the research that the OJT implementation service did not match expectations. From the various obstacles, suggestions for improvement are proposed.